Characterization of cooperative PS-oligo activation of human TLR9 - Adam J. Pollak; Luyi Zhao; Stanley T. Crooke (Elsevier, 2023)
Single-stranded phosphorothioate oligonucleotides (PS-oligos) can activate TLR9, leading to an innate immune response. This can occur with PS-oligos containing unmethylated CpG sites, the canonical motif, or PS-oligos that do not contain those motifs (non-CpG). Structural evidence shows that TLR9 contains two PS-oligo binding sites, and recent data suggest that synergistic cooperative activation of TLR9 can be achieved by adding two separate PS-oligos to cells, each engaging with a separate site on TLR9 to enhance TLR9 activation as a pair. Here, we demonstrate and characterize this cooperativity phenomenon using PS-oligos in human cell lines, and we introduce several novel PS-oligo pairs (CpG and non-CpG pairs) that show cooperative activation. Indeed, we find that cooperative PS-oligos likely bind at different sites on TLR9. Interestingly, we find that PS-oligos that generate little TLR9 activation on their own can prime TLR9 to be activated by other PS-oligos. Finally, we determine that previous models of TLR9 activation cannot be used to fully explain data from systems using human TLR9 and PS-oligos. Overall, we reveal new details of TLR9 activation, but we also find that more work needs to be done to determine where certain PS-oligos are binding to TLR9.